Pemanfaatan Media Power Point Untuk Meningkatkan Prestasi Belajar Tema Kegiatanku Di Masa Pandemi Covid -19 Siswa Kelas IC Dukuh Menanggal I/424 Kota Surabaya - Purbani Pudji Sayekti (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
The Power Point application is certainly no stranger to teachers, besides being easy to use Power Point is also facilitated with various menus that facilitate the learning process in class even though there are still teachers who use Power Point only as a substitute for blackboards but at least the teacher's efforts have been seen to be able to integrate technology in the learning process that is carried out in the classroom. By utilizing this power point learning media, there are several interesting things to use as a presentation tool for learning materials, namely being able to present various kinds of letters, colors, pictures and animations that can be processed more creatively and can be adapted to learning needs. The method used in this research is Classroom Action Research. The research was carried out in two cycles, one cycle consisting of lesson planning, learning implementation processes, observation and reflection activities. The researcher took the research subject of class students at SDN Dukuh Menanggal I/424 Surabaya City. The results showed that student learning outcomes in Learning Themes My Activities, using power point media increased each cycle. Recapitulation of learning outcomes Pre-cycle 57.83 then cycle I with an average value of 71.96 and cycle II with an average value of 83.71. So the results of this study indicate that learning the theme of my activity with the media power point approach can improve student learning outcomes, in learning the theme of my activity. In the future, more in-depth research is needed on other theme materials.